Use of innovative technologies at preparation of future specialists in area of hairdresser art - KHNYAZ’SKAYA, Viktoriya (Continuing Professional Education: Theory and Practice, 2019)
Innovation technologies of education which are including to the practical activity of KAHA were examined by the author. According to the examination of psychological pedagogical literature the author pointed some concepts “innovations”, “innovation studying”, “innovation activities” and other. It proved that innovations and creation are correlated.